2017
DOI: 10.3389/fmicb.2017.00213
|View full text |Cite
|
Sign up to set email alerts
|

The Complement System in Flavivirus Infections

Abstract: The incidence of flavivirus infections has increased dramatically in recent decades in tropical and sub-tropical climates worldwide, affecting hundreds of millions of people each year. The Flaviviridae family includes dengue, West Nile, Zika, Japanese encephalitis, and yellow fever viruses that are typically transmitted by mosquitoes or ticks, and cause a wide range of symptoms, such as fever, shock, meningitis, paralysis, birth defects, and death. The flavivirus genome is composed of a single positive-sense R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 84 publications
(107 reference statements)
8
58
0
Order By: Relevance
“…The activation of innate immunity leads to the activation of the complement cascade in response to viral infection. Complement components inhibit flavivirus infections such as Dengue, West Nile, and Yellow Fever at the replication level or by inducing inflammatory responses which lead to increases in the severity of disease . IPA predicted the activation of the complement cascade in our study by 24 hpi.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The activation of innate immunity leads to the activation of the complement cascade in response to viral infection. Complement components inhibit flavivirus infections such as Dengue, West Nile, and Yellow Fever at the replication level or by inducing inflammatory responses which lead to increases in the severity of disease . IPA predicted the activation of the complement cascade in our study by 24 hpi.…”
Section: Discussionsupporting
confidence: 49%
“…IPA predicted the activation of the complement cascade in our study by 24 hpi. During infection, viral NS1, one of the nonstructural proteins produced after cleavage of the viral polyprotein by host and viral proteases, aids viral pathogenesis by interaction with complement proteins and regulators involved in the complement cascade . Complement 4, which plays a role in the alternate and the classical complement pathways, is cleaved by C4‐NSI into two subunits, C4a (an anaphylatoxin) and C4b (opsonin) which aid in elimination of viral particles .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, preliminary experiments indicated that ZIKV infection of CD34 + HSPCs did neither inhibit cell growth nor prevented differentiation of erythroid and megakaryocytic cells (data not shown) as it is reported for other viruses such as DENV. [81][82][83][84] Thus, we speculate that thrombocytopenia and anemia in ZIKV-infected patients might be explained by cell damage due to an overshooting immune response 84,85 or ZIKV-induced impairment of blood vessel integrity or development [86][87][88] rather than by a direct interaction of ZIKV with erythroid and megakaryocytic cells. However, further investigations are crucial to unravel the connection of ZIKV pathogenicity and symptoms manifestation towards the prevention and cure of ZIKV infections.…”
Section: Discussionmentioning
confidence: 95%
“…The DENV, soluble circulating NS1 has been involved in several pathogenic mechanisms during the infection process. It has been reported NS1 can affect the complement pathway promoting the degradation of C4 protein, alters the coagulation system inhibiting the activation of prothrombin (reviewed by Conde et al, 2017). NS1 can also disrupts endothelium integrity, promoting an increase in the vascular permeability after internalization by endocytosis, that may be related to plasma leakage (Glasner et al, 2017; Puerta-Guardo et al, 2019; Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%